(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Highly variable drugs (HVDs), characterized by an intra-subject coefficient of variation (CV%) exceeding 30%, pose significant challenges in bioequivalence (BE) trials. Their variability stems from complex pharmacokinetics (PK), influenced by genetic polymorphisms in drug-metabolizing enzymes, transporters, and other pathways. These challenges often lead to larger sample sizes and higher costs. Pharmacogenetics, the study of genetic factors influencing drug response, offers a solution by stratifying participants based on genetic profiles to minimize variability. This paper discusses the role of pharmacogenetics in addressing these challenges, emphasizing its potential to optimize trial design, reduce sample sizes, and improve efficiency. Keywords include bioequivalence, pharmacogenetics, highly variable drugs, pharmacokinetics, genetic polymorphisms, and adaptive trial design.